The writing on the wall: Classroom context, curriculum implementation, and student learning in integrated, community-based science projects. - Venville, G.; Sheffield, Rachel; Rennie, Leonie; Wallace, J. (John Wiley & Sons, Inc., 2008)
In this study we examined curriculum integration in new ways by exploring the link between classroom context, the implementation of community-based, integrated science projects, and the subsequent student learning. The literature is inconsistent regarding the benefits of an integrated approach to curriculum. The research design was a multiple case study conducted in two classrooms in different schools. We employed a “worldly interpretive framework” that recognizes and embraces the importance of context in framing curriculum practices and outcomes. We found that similar projects in the two classrooms produced distinctly different (and equally valid) outcomes—focused either on bounded discipline-specific knowledge or, alternatively, on issues and problems that transcended disciplinary boundaries.